Effects on Photosystem II Function, Photoinhibition, and Plant Performance of the Spontaneous Mutation of Serine-264 in the Photosystem II Reaction Center D1 Protein in Triazine-Resistant Brassica napus L. - Sundby, C. (1993)
Wild-type and an atrazine-resistant biotype of Brassica napus, in which a glycine is substituted for the serine-264 of the D1protein, were grown over a wide range of constant irradiances in a growth cabinet. In the absence of serine-264, the function of photosystem II (PSII) was changed as reflected by changes in chlorophyll fluorescence parameters and in photosynthetic oxygen-evolving activity. The photochemical quenching coefficient was lower, showing that a larger proportion of the primary quinone acceptor is reduced at all irradiances. At low actinic irradiances, the nonphotochemical quenching coefficient was higher, showing a greater tendency for heat emission. Decreased rates of light-limited photosynthesis (quantum yield) and lower oxygen yields per single-turnover flash were also observed. These changes were observed even when the plants had been grown under low irradiances, indicating that the changes in PSII function are direct and not consequences of photoinhibition. In spite of the lowered PSII efficiency under light-limiting conditions, the light-saturated photosynthesis rate of the atrazine-resistant mutant was similar to that of the wild type. An enhanced susceptibility to photoinhibition was observed for the atrazine-resistant biotype compared to the wild type when plants were grown under high and intermediate, but not low, irradiance. We conclude that the replacement of serine by glycine in the D1 protein has a direct effect on PSII function, which in turn causes increased photoinhibitory damage and increased rates of turnover of the D1 protein. Both the intrinsic lowering of light-limited photosynthetic efficiency and the increased sensitivity to photoinhibition probably contribute to reduced crop yields in the field, to different extents, depending on growth conditions.